2009
DOI: 10.1590/s0103-21002009000100012
|View full text |Cite
|
Sign up to set email alerts
|

A família e a educação sexual dos filhos: implicações para a enfermagem

Abstract: OBJETIVO: Identificar como os pais vivenciam a educação sexual de seus filhos adolescentes. MÉTODOS: Pesquisa qualitativa descritiva exploratória, realizada em uma escola privada do município de Toledo, Paraná. Participaram do estudo 10 pais de alunos da 7ª e 8ª séries. Os dados foram coletados através de entrevista semi-estruturada e analisados conforme o método do Discurso do Sujeito Coletivo. RESULTADOS: Os pais fizeram algumas considerações sobre o modo como orientam os filhos sobre sexualidade, entre elas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
20

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 2 publications
0
9
0
20
Order By: Relevance
“…Facing the evidences proceeding from studies in the area of STD/AIDS prevention and development of instruments/scales it is perceivable that studies which comprise this reality in the most different contexts are relevant as they contribute to rethink the educational and preventive practices in the scope of the family health, beyond the (re)creation of adequate technologies for such a reality (5) . This fact justifies the necessity of validity and precision studies, since its use involves situations in which the nurse, in that case, will evaluate determined aspects that might interfere with the life quality and health of the adolescents (6) .…”
Section: Introductionmentioning
confidence: 99%
“…Facing the evidences proceeding from studies in the area of STD/AIDS prevention and development of instruments/scales it is perceivable that studies which comprise this reality in the most different contexts are relevant as they contribute to rethink the educational and preventive practices in the scope of the family health, beyond the (re)creation of adequate technologies for such a reality (5) . This fact justifies the necessity of validity and precision studies, since its use involves situations in which the nurse, in that case, will evaluate determined aspects that might interfere with the life quality and health of the adolescents (6) .…”
Section: Introductionmentioning
confidence: 99%
“…The latter study was conducted with parents who had higher education, some with graduate degrees, and an income of 11 to 20 minimum wages to verify how they dealt with sexual education of their young children, and found that the parents reported that they provided guidance through frank dialogue (15) . Another study (16) that conducted a research with a family who lived in precarious life conditions in the outskirts of Fortaleza (CE) found that the mother did not talk about sex because she feared that the conversation would induce her girls to initiate sexual activity.…”
Section: Discussionmentioning
confidence: 99%
“…Porém mesmo a escola ampliando a discussão do assunto, é importante que a família em casa também continue o trabalho, para que não se torne algo proibido e também para que a família possa estar o mais consoante possível com o aprendizado de seus fi lhos e fi lhas (Almeida & Centa, 2009).…”
Section: A "Orientação Sexual" Vista Através Das Lentes Dos Pcns: Impunclassified